2018
DOI: 10.1021/acsami.8b18638
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble and Low-Toxic Ionic Polymer Dots as Invisible Security Ink for MultiStage Information Encryption

Abstract: Nanodots are attractive stimuli-responsive luminescence materials for anti-counterfeiting and information encryption. However, their applications are limited by low water solubility and single-mode information identification by naked eyes under UV light illumination. Herein, we report one type of new nanodots, main-chain imidazoliumbased ionic polymer dots (IPDs). There is no edge effect in IPDs, and the ionic groups are homogenously distributed in the entire dot. IPDs exhibit high water solubility, good stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Miller and co‐workers have demonstrated that cross‐linked imidazolium networks with a combination of ionene and polyelectrolyte character can be formed from divinyl‐functionalized ILs and thiols through thiol–ene chemistry . Hypercrosslinked imidazolium ionenes have been synthesized from species such as 1,1′,1″‐(1,3,5‐benzenetriyl) trisimidazole and 2,4,6‐tris[4‐(bromomethyl) phenyl]‐1,3,5‐triazine …”
Section: Imidazolium Ionenesmentioning
confidence: 99%
“…Miller and co‐workers have demonstrated that cross‐linked imidazolium networks with a combination of ionene and polyelectrolyte character can be formed from divinyl‐functionalized ILs and thiols through thiol–ene chemistry . Hypercrosslinked imidazolium ionenes have been synthesized from species such as 1,1′,1″‐(1,3,5‐benzenetriyl) trisimidazole and 2,4,6‐tris[4‐(bromomethyl) phenyl]‐1,3,5‐triazine …”
Section: Imidazolium Ionenesmentioning
confidence: 99%
“…The optical absorption and band gaps of Re-POMP and Re-POMP-IL1.0 were studied by UV/Vis diffuse reflectance spectra as illustrated in Figure 4(a) , in which the good visible-light absorption of polymers was observed. Compared with Re-POMP, Re-POMPIL1.0 shows about 50 nm blue shift in absorption onset, probably being ascribed to the existence of IL reduce the conjugated structures [ 41 ]. According to their absorption edges, the optical band gaps of Re-POMP and Re-POMP-IL1.0 were obtained from the Tauc plots, in which the band gap is broadened as the presence of IL unit (Figure S7 , see Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
“…In the system of water-based ink, the stability of pigments represents an important variable, crucial for their application potential [ 13 ]. Therefore, the as-prepared PTSA-SiNP material was applied to the water-based fluorescent anti-counterfeiting ink, and the fluorescence stability in the application process was tested.…”
Section: Resultsmentioning
confidence: 99%
“…In the past several years, various fluorescent materials have been explored in the preparation of water-based anti-counterfeit ink, such as organic fluorescent dyes [ 4 , 5 ], rare-earth luminescent materials [ 6 , 7 , 8 ], carbon dots [ 9 , 10 , 11 , 12 ], organic polymers [ 13 , 14 ] etc. Compared with other fluorescent materials, organic fluorescent dyes have the advantages of easy access to raw materials, more variety, bright colors and a low cost.…”
Section: Introductionmentioning
confidence: 99%